Pelatihan Sistem Air Conditioning Pesawat Boeing 737-200 Bagi Siswa Jogja Flight - Arif Pambekti; Luqman Al Huda; Bah Evan; Amrisal Kamal Fajri; Erwan Tri Efendi (AMMA : Jurnal Pengabdian Masyarakat, 2025)
Partners in this community service activity are Jogja Flight students. The goals and targets to be achieved in community service for Jogja Flight students are to increase students' knowledge about one of the aircraft systems, namely air conditioning. With this activity, it is hoped that it can increase students' provisions in job competition in the aviation world. To achieve the goals and targets of this community service program, partners are given training on air conditioning systems in the form of writing, pictures or videos during this activity. After this activity, Jogja Flight students have an additional ability of 90% which was initially only 17% about the Boeing 737-200 aircraft air conditioning system which is useful as added value when working later.